RELEVANSI KARAKTER YESUS DALAM MATIUS 11:29 TERHADAP PELAYAN MUSIK GEREJAWI MASA KINI - Susanto, Viki; Kiamani, Andris (STT-RAI Batam, 2025)
In today's Christian worship celebrations, music has an almost inseparable role in the course of worship. However, it is equally important that the minister of church music should have a character that reflects the character of Jesus. If a church musician does not exhibit the character of Christ, he or she can become a stumbling block to the congregation. This article aims to examine the character of Jesus in His ministry based on Matthew 11:29 and relate it to the role of God's servants in the field of church music. Thus, church musicians are expected not only to serve based on their musical skills, but also with a character that is in accordance with the teachings of Christ. This research uses a qualitative method with a literature study approach from various sources, such as journals, books, and the Bible. The results showed that Jesus' character has relevance for today's church music. First, church musicians must learn to be faithful and obedient to God in their ministry. Second, they need to have a meek attitude to create harmony in the music team. Third, a humble attitude should also be developed in every aspect of their ministry. This research has shown that the character of Jesus forms the spiritual foundation for church musicians, creating a harmonious, humble, and faithful ministry.